2015
DOI: 10.1002/joc.4268
|View full text |Cite
|
Sign up to set email alerts
|

Longshore wind, waves and currents: climate and climate projections at Ninety Mile Beach, southeastern Australia

Abstract: It is shown that Lakes Entrance, a township located at the northern end of Ninety Mile Beach in southeastern Australia, is situated in a region that may experience noticeable changes in longshore wind, wave and ocean currents compared to present day climate variability as a consequence of the southward shifting subtropical ridge (STR) predicted in global climate change models. These changes could modify sediment transport in the littoral zone and impact the coastline position. Thirty-year hindcasts of winds, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…O'Grady et al (2015) has shown that the change in both wind-driven currents and waves in south-eastern Australia may lead to complex seasonal changes in longshore sediment transport with subsequent impacts on the near shore region.…”
Section: Projected Changes To Extreme Sea Levelsmentioning
confidence: 99%
“…O'Grady et al (2015) has shown that the change in both wind-driven currents and waves in south-eastern Australia may lead to complex seasonal changes in longshore sediment transport with subsequent impacts on the near shore region.…”
Section: Projected Changes To Extreme Sea Levelsmentioning
confidence: 99%
“…Wave setup is an increase in mean water level due to the cross-shore Other coastal attributes, such as continental shelf width, bathymetric depth, coastline 125 orientation in relation to prevailing weather conditions, headlands, estuaries and shoreline 126 slopes, also influence extreme sea levels. The wider shelf regions along the tropical and much 127 of the southern Australian coastline ( Figure 3) are conducive to larger storm surges and tidal 128 ranges whereas the narrower shelves along the southeast, southwest and parts of the 129 southern coastline are exposed to wave-driven coastal extremes. Coral reefs, found along the 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63…”
mentioning
confidence: 99%
“…35 Lowe et al, 2009]. Changes to wind-driven coastal currents, which could be considered using the modelling framework presented in this study (but is beyond the scope of this paper), is also potentially important in the context of coastal erosion and shoreline change [Gornitz, 1991;O'Grady et al, 2015].…”
Section: Summary and Concluding Discussionmentioning
confidence: 99%